Detecting bid-rigging in public procurement: A cluster analysis approach - Mihail Busu; Cristian Busu (Administrative Sciences, 2021)
This paper analyses the public procurement auctions for snow removal contracts to find out whether bid-rigging occurred. Due to the limited participation in the auction processes, detection of anticompetitive agreements was possible. The econometric analysis used in our study supported the findings of a cartel agreement. Cluster analysis, statistical hypothesis, normality and symmetry and nonparametric tests reveal two types of auctions: competitive and noncompetitive bids. The aim of this paper is to analyze the public procurement auctions with nonparametric statistical methods. Our findings are in line with the literature in the field.
Keywords: 350; bid-rigging; cluster analysis; hypothesis testing; public administration; public procurement